2013
DOI: 10.1017/s0022215113000273
|View full text |Cite
|
Sign up to set email alerts
|

Does tonsillectomy improve quality of life in adults? A systematic literature review

Abstract: Eight studies were identified. The Glasgow Benefit Inventory and the Short Form questionnaire were the main tools used to assess quality of life changes. Tonsillectomy is likely to improve the overall quality of life as it particularly improves patients' physical and general health. The social benefits of tonsillectomy appear to be non-significant. The effects are likely to be long-lasting and have a greater impact on younger patients. The presence of coexisting chronic conditions and the severity of infective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 12 publications
1
23
0
1
Order By: Relevance
“…Within each group, in the CHT and separately in the PTA group, the correlation of serology parameters at T-1 with the functional outcome at T180 was examined with via Pearson product–moment correlations. In reference to the results of previous studies [6], the four most important functional outcome subscales (GBI social subscale; GBI physical subscale; SBTI resources subscale; SBTI benefit subscale) were selected for multiple comparisons (Additional file 1: Table S1 and Additional file 2: Table S2). The Bonferroni correction was used to adjust the P value while performing multiple comparisons: As four outcome subscales were examined, the level of significance was set at p < 0.0125 (=0.05/4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within each group, in the CHT and separately in the PTA group, the correlation of serology parameters at T-1 with the functional outcome at T180 was examined with via Pearson product–moment correlations. In reference to the results of previous studies [6], the four most important functional outcome subscales (GBI social subscale; GBI physical subscale; SBTI resources subscale; SBTI benefit subscale) were selected for multiple comparisons (Additional file 1: Table S1 and Additional file 2: Table S2). The Bonferroni correction was used to adjust the P value while performing multiple comparisons: As four outcome subscales were examined, the level of significance was set at p < 0.0125 (=0.05/4).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the severity of the systemic reaction that might be beyond this chronic focal inflammation is not specified yet and taken into account for decision making for surgery. Nevertheless, even with limited criteria for patient selection for tonsillectomy the rates of satisfaction with the outcome following surgery are high [4-6]. Although a frequent illness, the literature on surgery for recurrent tonsillitis is limited, especially on surgery in adults [1].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review, Andreou and coworkers reported that the SF- 36 and the Glasgow Benefit Inventory are most frequently used [20]. The SF-36 is a universal HRQL assessment tool with well documented psychometric characteristics [6].…”
Section: Discussionmentioning
confidence: 99%
“…Erwachsene -Die TE kann die Zahl rezidivierender akuter Tonsillitiden und deswegen notwendiger erapien/Arztbesuche reduzieren und die Lebensqualität steigern [10,11]. -Je schwerer erkrankt und je jünger die Patienten sind, umso besser ist der E ekt der TE.…”
Section: Kinderunclassified